Data Warehouse Systems [electronic resource] : Design and Implementation / by Alejandro Vaisman, Esteban Zimányi. - Vaisman, Alejandro (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014., 2018)
XVI, 625 p. 133 illus. online resource.